2020
DOI: 10.1177/1535370220981006
|View full text |Cite
|
Sign up to set email alerts
|

Roles of kisspeptin in IVF/ICSI-treated infertile women and in human granulosa cells

Abstract: Kisspeptin, a crucial central regulator of reproduction, has been used as a trigger in in vitro fertilization (IVF) treatment. This study aimed to investigate the roles of kisspeptin in IVF treatment in infertile females ( n = 30); and in steroidogenesis in human granulosa-like tumor cell line (KGN). In the human study, blood was collected at three time points including (1) the beginning of gonadotropin stimulation (Phase I), (2) around eight days after gonadotropin stimulation (Phase II), and (3) on the day o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 64 publications
0
4
0
Order By: Relevance
“…However, early menopause is a potential driver for primary infertility through decrease in plasma Kisspeptin and increase in KISS1 gene expression in the blood. This finding justifies the Kisspeptin or KISS1R agonist supplementation in women already showing promise [35,[67][68][69][70][71][72][73] , which could also be helpful for PIW with history of early menarche. KISS1 gene expression in the blood is central to the role of the Kisspeptin system and may be a significant regulator of its effect within the human blood;…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…However, early menopause is a potential driver for primary infertility through decrease in plasma Kisspeptin and increase in KISS1 gene expression in the blood. This finding justifies the Kisspeptin or KISS1R agonist supplementation in women already showing promise [35,[67][68][69][70][71][72][73] , which could also be helpful for PIW with history of early menarche. KISS1 gene expression in the blood is central to the role of the Kisspeptin system and may be a significant regulator of its effect within the human blood;…”
Section: Discussionmentioning
confidence: 54%
“…The findings of this present study add to the justification for Kisspeptin supplementation for GnRH stimulation and suggest that supplementation may be needed by PIW who present with a history of early menarche. Kisspeptin supplementation has been used in clinical trials as KP-10 and KP-54 isoforms in females with hypothalamic amenorrhoea [67][68][69] , PCOS [35] , or infertile women requiring IVF, with a need to prevent OHSS or stimulate ovulation [70][71][72][73] . The trials mentioned above have shown no noticeable side effects across various doses, times, and routes of administration.…”
Section: Discussionmentioning
confidence: 99%
“…For humans, information regarding age, body weight, BMI, the duration of the menstrual cycle, the duration of ovarian stimulation, serum FSH, and serum LH in the three phases of the IVF/ICSI treatment were presented as the 25th percentile, median, and 75th percentile. The mean values of these parameters and the differences between successful and unsuccessful pregnancies were reported in a previously published paper [19]. Other data are shown as the mean ± standard deviation (SD).…”
Section: Discussionmentioning
confidence: 96%
“…In accordance with the manufacturer's instructions, the cDNA was amplified as follows: 5 min at 25 • C, 30 min at 42 • C, and 5 min at 85 • C using the MasterCycler gradient (Eppendorf, Hamburg, Germany), which then was kept at −20 • C until RT-PCR analysis. The primer sequences of the FSHR, CYP19A1, and HPRT1 genes were designed by the authors and published previously [19] as follows: FSHR (240 base pairs): forward-5 AGGAATGC-CATTGAACTGAGGT 3 , reverse-5 CAGATATTGAAGGTTGGGAAGGT 3 ; CYP19A1 (267 base pairs): forward-5 AGCAAGTCCTCAAGTATGTTCCAC 3 , reverse-5 GTC-CACATAGCCCGATTCATT 3 ; and HPRT1 (156 base pairs): forward-5 CCTGGCGTCGT-GATTAGTGA 3 , reverse-5 CCATCTCCTTCACATCTCG 3 .…”
Section: Rna Extraction and Real-time Polymerase Chain Reaction (Rt-pcr)mentioning
confidence: 99%